Orange‐fleshed sweetpotato (OFSP) puree for fried and baked products in Kenya, Uganda, and Malawi project. 2019‐2020 Workplan review meeting. - CGIAR Research Program on Roots, Tubers and Bananas (International Potato Center, 2019)
The CGIAR Research Program on Roots, Tubers and Bananas (RTB) funded the International Potato Center (CIP) with a scaling grants to accelerate the use of orange-fleshed sweetpotato (OFSP) puree in Kenya, Malawi and Uganda. The two‐year (2019–21) project targets both formal (processors) and informal (street vendors) sectors with OFSP puree as a major ingredient to reduce the use of wheat flour and to enrich the products with vitamin A.